2017
DOI: 10.3847/1538-4357/834/1/56
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Properties of Solar Active Regions That Govern Large Solar Flares and Eruptions

Abstract: Solar flares and coronal mass ejections (CMEs), especially the larger ones, emanate from active regions (ARs). With the aim to understand the magnetic properties that govern such flares and eruptions, we systematically survey all flare events with GOES levels of ≥ M5.0 within 45• from disk center between May 2010 and April 2016. These criteria lead to a total of 51 flares from 29 ARs, for which we analyze the observational data obtained by the Solar Dynamics Observatory. More than 80% of the 29 ARs are found t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
123
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(149 citation statements)
references
References 72 publications
21
123
3
Order By: Relevance
“…Fig. 6 of Toriumi et al 2017). That means that they originated from a minor ("satellite") bipolar magnetic flux concentration located in the periphery of an AR.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fig. 6 of Toriumi et al 2017). That means that they originated from a minor ("satellite") bipolar magnetic flux concentration located in the periphery of an AR.…”
Section: Resultsmentioning
confidence: 99%
“…Out of these, 12 (∼27%) events were confined (7 M-and 5 X-flares) and 32 (∼73%) were eruptive (18 M-and 14 X-flares). In comparison to Toriumi et al (2017), we classify two events differently. Firstly, we classify event no.…”
Section: Event Samplementioning
confidence: 99%
“…Given our framework, our study is thus limited in terms of size and complexity of active regions that we cannot explore: the reliability of eruptive indicators is tested only for a given class of active region size and complexity. Nonetheless, it is worth noting that a recent study by Toriumi et al (2017) concludes that a complex d-sunspot is not a necessary condition for flaring ARs, even for the X-class flares. Thus, this kind of controlled study is important in the sense that the size and the complexity of an active region are not discriminant parameters for eruptivity: small active regions can still produce flares, while two active regions in the same size and complexity range do not necessarily have the same flaring likelihood.…”
Section: Scalingmentioning
confidence: 97%
“…Determining whether or not the net electric current I AE net is neutralized over individual polarities of ARs is crucial for some theoretical flare and CMEs models (e.g., Melrose 1991;Parker 1996;Titov & Démoulin 1999;Forbes 2010). If the AR currents are fully neutralized, the net current integrated over one photospheric polarity is set to zero.…”
Section: Current Propertiesmentioning
confidence: 99%
“…Recent statistical study of flare ribbons by Toriumi et al (2017) demonstrated that compared to confined flares, the eruptive flares showed a larger ratio of the ribbon area to AR area. According to the authors, this ratio reflects the relative scale of the magnetic field involved in reconnection compared to the ambient field that is an obstacle for fast and powerful eruption.…”
Section: Quasi-circular Secondary Ribbonmentioning
confidence: 99%